Synthesis, Identification, and Biological Activity Investigation of New Pyrazolines Derived from Vanillin - Ali, Raniah T.; Dawood, Rafid S. (Iraqi Journal of Science, 2024)
This work includes the synthesis of new pyrazoline derivatives 6-20 over two steps. The first step included a condensation between vanillin and various aromatic ketones (acetophenone, p-nitroacetophenone, p-chloroacetophenone, p-bromoacetophenone, and 2-acetylnaphthalene) to provide the corresponding chalcone derivatives 1-5 in high yields (up to 93%). The second step involved a reaction of 1-5 with hydrazine hydrate, phenyl hydrazine, and p-nitrophenyl hydrazine, which gave the desired products 6-20 in yields ranging from 60 to 85%. The structures of the prepared compounds were confirmed by FT-IR and 1H NMR spectroscopy. A few of the produced compounds were tested for antibacterial and antioxidant properties.